Avaliação in vitro da potencial atividade citotóxica e genotóxica de metalocomplexos à base de rênio - Teixeira, Maria Henriqueta Silvestre (2023)
Cancer is a challenging disease in the healthcare field, characterized by the uncontrolled growth of defective cells. The search for effective treatments is constant due to the global increase in cancer incidence and mortality. Conventional treatments such as surgery, radiotherapy, chemotherapy, and biological therapy face challenges like significant side effects and tumor resistance. In this context, metal complexes emerge as a promising therapeutic approach. The methodology used in the study involved the cultivation of different cell lines, including cervical adenocarcinoma, prostate epithelial tissue, murine melanoma, and murine fibroblast. Metal complexes were tested to evaluate their cytotoxic potential through the resazurin reduction assay. The selectivity index was calculated to verify the compounds' selectivity towards tumor cells. The DNA interaction and cleavage assay by electrophoresis were developed, where rhenium complexes were combined with plasmid DNA. Molecular docking analyzed the interaction of complexes with DNA and BSA macromolecules. Cell cycle progression was evaluated by flow cytometry, and an apoptosis assay was conducted to verify if the complexes induce this process in tumor cells. This study investigates the therapeutic potentials of three rhenium complexes ([Re(CO)3(phen)(py)]+, [Re(CO)3(dpq)(py)]+, and [Re(CO)3(dppz)(py)]+) in tumor cells, focusing on the cervical cancer HeLa lineage. Cytotoxicity assessment revealed that the complexes demonstrate moderate toxicity against HeLa cells, with IC50 values below 50 µM, positioning them as promising candidates. The Selectivity Index (SI) was calculated to evaluate the complexes' ability to distinguish between tumor and non-tumor cells. The results indicated that all three complexes had an SI below two, suggesting the need for additional strategies such as targeted delivery or bioisosterism to enhance selectivity. Molecular docking was employed to investigate the complexes' interactions with BSA protein and DNA, considering a representation of the biological environment. Docking results revealed favorable interactions at tryptophan 134 and 213 sites of BSA and also with the DNA minor groove, providing insights into possible action mechanisms of the complexes. DNA interaction was confirmed in vitro, as the complexes could cleave Plasmid DNA. It was also observed that all complexes interfere with the cell cycle and induce apoptosis. Comparing the obtained results with the literature review highlighted the relevance of the studied complexes, as their IC50 values were lower than those of previously described rhenium complexes. This work not only contributes to the evaluation of new antitumor agents but also enriches the knowledge about the interaction of these complexes with proteins and DNA, laying the foundation for future investigations in the field of antitumor chemotherapy. Ultimately, the research presents a promising perspective for the development of rhenium compounds as innovative therapeutic candidates in cancer treatment.